Marine diatom isolation, identification and investigation of nutrient effects on the diatom growth - Cinar, Sait; Ozcimen, Didem; Yilmaz, Mete (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
Microalgae are new generation raw material resources that have been attracting much attention in recent years and have utilization potential in health, food, cosmetics, environment and biofuel production areas. In this study, diatoms, an important microalgal group both due to their abundance and functions, were targeted and an isolation study was carried out with the water samples collected from the Mudanya shores of the Marmara Sea. Isolated diatom was identified as Pleurosigma sp. by DNA sequencing. Diatom's cell density showed statistically positive correlation with increase in silicon and nitrogen when isolated Pleurosigma sp. was cultivated in nutrient solutions containing nitrogen, phosphorus and silicon at different concentrations, but cell density was observed to reach a maximum level at 0.0096 mM phosphate concentration. In the characterization studies, it was observed that the diatom contained significant amounts of ash and silica and diatom's fatty acid profile overlapped with the fatty acid profiles of the frequently studied diatoms in literature.
Keywords: Microalga; diatom; pleurosigma sp.; isolation; ENVIRONMENTAL-FACTORS; BIOCHEMICAL-COMPOSITION; FATTY-ACID; MICROALGAE; PRODUCTS; SILICATE; ALGAE; PHOTOSYNTHESIS; PHYTOPLANKTON; ENHANCEMENT; Engineering